Prognostic value of O‐6‐methylguanine–DNA methyltransferase (MGMT) protein expression in glioblastoma excluding nontumour cells from the analysis. (28th June 2017) - Dahlrot, R. H.; Dowsett, J.; Fosmark, S.; Malmström, A.; Henriksson, R.; Boldt, H.; de Stricker, K.; Sørensen, M. D.; Poulsen, H. S.; Lysiak, M.; Söderkvist, P.; Rosell, J.; et al.
Abstract : Aims: It is important to predict response to treatment with temozolomide (TMZ) in glioblastoma (GBM) patients. Both MGMT protein expression and MGMT promoter methylation status have been reported to predict the response to TMZ. We investigated the prognostic value of quantified MGMT protein levels in tumour cells and the prognostic importance of combining information of MGMT protein level and MGMT promoter methylation status. Methods: MGMT protein expression was quantified in tumour cells in 171 GBMs from the population‐based Region of Southern Denmark (RSD)‐cohort using a double immunofluorescence approach. Pyrosequencing was performed in 157 patients. For validation we used GBM‐patients from a Nordic Study (NS) investigating the effect of radiotherapy and different TMZ schedules. Results: When divided at the median, patients with low expression of MGMT protein (AF‐low) had the best prognosis (HR = 1.5, P = 0.01). Similar results were observed in the subgroup of patients receiving the Stupp regimen (HR = 2.0, P = 0.001). In the NS‐cohort a trend towards superior survival (HR = 1.6, P = 0.08) was seen in patients with AF‐low. Including MGMT promoter methylation status, we found for both cohorts that patients with methylated MGMT promoter and AF‐low had the best outcome; median OS 23.1 and 20.0 months, respectively. Conclusion: Our data indicate that MGMT protein expression in tumour cells has an independent prognostic significance. Exclusion of nontumour cells contributed to a more exact analysis of tumour‐specific MGMT protein expression. This should be incorporated in future studies evaluating MGMT status before potential integration into clinical practice.